Research on the Way of Village Renovation and Renewal — Taking Cuiwei Historic District As an Example - Junzhang Chen; Yile Chen; Liang Zheng (PT FORMOSA CENDEKIA GLOBAL, 2022)
With the rapid development of science and technology, since the reform and opening up, the speed of urbanization construction has been accelerating. Zhuhai City has steadily promoted the transformation of old factories, old towns and old villages, which in turn promoted the process of urban renewal and realized the economic development of the city. Take off, promote the transformation and upgrading of industries, and improve people's living standards. This study takes the former Shancuiwei Historic District as an example, and gives corresponding policy suggestions for village renovation and renewal and future development.